Anaesthetic rooms: a systems approach to improving design and practice in the United Kingdom - Velzen, Jeena (2017)
The use of anaesthetic rooms as the standard site of anaesthetic induction in the United Kingdom has been criticised and debated over several decades, and yet practice has remained largely unchanged. The impacts of the anaesthetic room on cost, efficiency, patient experience, and patient safety are either conflicting or unknown.